Challenges and coping strategies of parents of children with autism on the Kenyan coast. - Gona, J; Newton, C; Rimba, K; Mapenzi, R; Kihara, M; Vijver, F; Abubakar, A (James Cook University, 2016)
INTRODUCTION: Research on the challenges of raising a child with autism is mostly conducted in Europe, North America and Australia, and has revealed that parents have to come to terms with living with a lifelong developmental disability. In addition, parents are faced with numerous concerns, such as caring burdens, poor prognosis, and negative public attitudes. Virtually no research has been conducted in Africa on this subject. METHODS: Thirty-seven interviews and eight focus group discussions were conducted with parents of children with autism and professionals in regular contact with these parents from rural and urban counties of the Kenyan coast. The study investigated challenges faced by parents and how they cope with those challenges. A purposive-convenience sampling procedure was used in selecting the study participants. A digital recorder was used to record all the interviews and focus group discussions. Transcriptions were done in Swahili, translated into English, and then imported to the NVivo software program for content analysis. RESULTS: The results indicate that parents of children with autism on the Kenyan coast experience common challenges including stigma, lack of appropriate treatment, financial and caring burdens regardless of their religious and cultural backgrounds. Coping strategies applied by parents comprised problem-focused aspects that involve diet management and respite care, and emotion-focused aspects that consist of beliefs in supernatural powers, prayers and spiritual healing. CONCLUSIONS: This qualitative study reveals a range of challenges that could have significant impact when caring for a child with autism. Coping strategies applied by parents target the physical health of the child and the psychological wellbeing of the parent. Consideration of these outcomes is vital as they could impact the initiation of a community-based rehabilitation service delivery in rural settings where parents play an active role.